Message from the Chief Editor - Editor, Chief (Journal of Technical Education and Training, 2016)
Welcome to issue 1, volume 8 of the Journal of Technical Education and Training (JTET). I am happy to present six original papers in this issue that share some aspects of TVET practices in Malaysia, Nigeria, India and Iran. Concerns highlighted in this issue include effective teaching, achievement of learning outcomes, training transfer, and health and safety at work. One of the indicators of a civilised society is in how well they take care of the environment in which they live. The TVET sector shoulders some responsibility in this area and they need to prepare future workforce who have the capability to care and develop our world in a sustainable manner. Thus, the readiness of TVET institutions to shoulder this responsibility is of great concern. The first paper by Peter, Libunao, and Abdul Latif looks at how well Malaysian public community colleges are integrating education for sustainable development into their curriculum. To achieve sustainable development goals, participating workforce must have holistic attributes; possessing the necessary technical skills as well as generic skills. Thus, as preparation, TVET programmes are expected to give equal emphasis on generic and technical learning outcomes. The second and third paper look at generic or soft skills development of TVET students. In the second paper, Amiruddin, Ngadiman, Abdul Kadir, and Saidy reports on the current status of soft-skills among TVET trainees in one of the major providers of Malaysian skilled workforce, the Advanced Technology Training Centres. The third paper by Zare, Sarikhani, Salari and Mansouri looks at the means to develop a particular type of generic skills i.e., creativity. Specifically, the paper discusses the effectiveness of e-learning medium in developing creativity among future chemists in Iran. In the fourth paper, one particular teacher factor is investigated with respect to performance of TVET students. The paper which is authored by Igberadja investigates if gender of TVET teachers is associated with students’ performance. With increasing expectations on TVET teachers to deliver effectively, real concern is emerging on the state of their health and safety. In the fifth paper, Dankade, Bello and Deba studied the potential effect of work related stress on job performance among vocational technical teachers in Nigeria. Understanding and managing teachers’ work related stress is important as stress can affect their productivity; positively if stress is short term, and negatively if stress continues over a long period. At the workplace, training effectiveness is a major concern as organizations invest a lot of money on trainings and retraining for reskilling or up skilling. To provide effective training, organisations need to know the factors that influence training effectiveness. The way to identify these factors is precisely the focus of the last paper which is authored by Rajaprasad and Chalapathi who discuss the means of ascertaining the influencing factors in transfer of safety training skills in Indian construction organizations. Overall, this issue has highlighted concerns of TVET practitioners that relate to institutional and workplace practices which I hope contribute to better knowledge and understanding of TVET practices globally. For the timely publication of this issue, I would like to extend my gratitude to all authors who choose to publish with JTET and to all reviewers who have volunteered their expert services - amidst their busy schedule - in ensuring the quality of published papers. Last but not least, in this Holy month of Ramadan, I would like to wish Ramadan Kareem and Eid Mubarak to all Muslims. Professor Dr. Maizam Alias Chief Editor